Beef Alliances: A Basic Economic Overview - Thomas E. Anton (EDIS)
This is EDIS document FE 337, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published May 2002.